BUILDING THE STUDENTS’ CHARACTERS THROUGH MORAL VALUES CONTAINED IN THE STORY OF AJISAKA, A FOLKTALE FROM CENTRAL JAVA: Array - Sri Rejeki Pramudyaardhani; Moh. Ilhami Hakim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Peradaban, 2021)
Folktales are important media which can be used to build the students’ characters, as they are rich of moral values. One of well-known folktales in Central Java is the story of Ajisaka. This story is the origin of Javanese letters named Dhentawiyanjana or Carakan Letters (ha, na, ca, ra, ka, and so forth). There are four characters contained in this story, namely Ajisaka, his faithful followers (Dora and Sembada), and Prabu Dewatacengkar, from whom this story is harvesting moral values. This article analyses some moral values contained in the story of Ajisaka, a folktale from Central Java, to build the students’ characters. There are some characters of the students which are expected to be built after they read or listen to the story of Ajisaka. The moral values contained are about leadership, bravery, helpfulness, faithfulness, honesty, and responsibility.